COVID-19 pandemic and its influence on mental health of healthcare professionals in Nepal - Bhattarai, Robin; Yumnam , Joshila Chanu; Chhantyal , Kishor; Rai, Karuna; Chaudhary, Manoj Kumar; Dahal, Shivir Sharma; Thapa, Suman (Eastern Green Neurosurgery, 2021)
Given the unprecedented global public health crisis due to the covid-19 pandemic, it is important to recognize the psychological impact on health care professionals. Previous experiences from the smaller scale epidemiology and new literature on COVID-19 have shown that increased pressure on healthcare professionals is associated with rise in the psychological incidence rates. We have described the psychological burden of the covid-19 pandemic on health care workers in Nepal and reviewed the literature on the impact of previous epidemics on front-line health care workers. In addition, we discussed potential triggers and measures to minimize the front-line psychological pressure to deal with this biological threat.